2016
DOI: 10.1055/s-0035-1566120
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobins, Hemorphins, and 11p15.5 Chromosomal Region in Cancer Biology and İmmunity with Special Emphasis for Brain Tumors

Abstract: In systemic cancers, increased hemolysis leads to extracellular hemoglobin (HB), and experimental studies have shown its provoking role on tumor growth and metastasis. However, investigations have shown that HB chains presented by tumor vascular pericytes or serum protein complexes of HB could also induce antitumor immunity, which may be harnessed to treat refractory cancers and brain tumors. Mounting recent evidence shows that expression of HBs is not restricted to erythrocytes and that HBs exist in the cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 104 publications
(172 reference statements)
1
3
0
Order By: Relevance
“…An HBB‐derived peptide exerted cytotoxicity to human neuroblastoma cells in vitro and inhibited metastasis formation of neuroblastoma xenografts in vivo 11 . The present study and other studies 44‐48 indicated that hemoglobin and hemoglobin‐derived fragments could be classified as moonlighting proteins characterized by their capacity to perform multiple physiologic tasks, including anticancer functions.…”
Section: Discussionsupporting
confidence: 55%
“…An HBB‐derived peptide exerted cytotoxicity to human neuroblastoma cells in vitro and inhibited metastasis formation of neuroblastoma xenografts in vivo 11 . The present study and other studies 44‐48 indicated that hemoglobin and hemoglobin‐derived fragments could be classified as moonlighting proteins characterized by their capacity to perform multiple physiologic tasks, including anticancer functions.…”
Section: Discussionsupporting
confidence: 55%
“…This peptide holds multiple biological activities including a role in the maintenance of homeostasis [28]. Recently, the expression of hemoglobin chains in neurons and glial cells, in endothelial and tumor vessels, and the potential role of hemoglobin and hemorphin peptides within brain tumors [29] shed a new light on the investigation of this nonepithelial protein and its fragment. The fragment 25-48 of serum albumin was detected in four samples, and given its frequent identification in biological fluids and tissues [25], this fragment could have a biological significance.…”
Section: Resultsmentioning
confidence: 99%
“…A study demonstrated significantly lower expression levels of TRIM3 in lung cancer tissue compared to normal lung tissue, with its expression level closely correlating with the clinical and pathological characteristics of lung cancer. Further experiments evidenced TRIM3’s ability to inhibit lung cancer cell proliferation and invasion and induce apoptosis (Altinoz et al 2016 ). Additionally, TRIM3 can also regulate the metabolism of lung cancer cells, curtailing metabolic pathways such as glycolysis and oxidative phosphorylation, thus hindering the growth and invasion of lung cancer cells.…”
Section: The Role Of Trim3 In Antitumorigenesis and Tumor Developmentmentioning
confidence: 99%